Comparing neurocognition in severe chronic schizophrenia and frontotemporal dementia. (September 2014) - Chan, Hui-Minn; Stolwyk, Rene; Kelso, Wendy; Neath, Joanna; Walterfang, Mark; Mocellin, Ramon; Pavlis, Alexia; Velakoulis, Dennis
Objective: Previous research has suggested cognitive similarities between schizophrenia and frontotemporal dementia. In the current study, we compared neurocognition in a group of hospitalised patients with chronic schizophrenia, who may have a more severe form of schizophrenia resembling Emil Kraepelin's dementia praecox, with patients with frontotemporal dementia. We hypothesised minimal group differences in cognitive performance, and a large overlap in between-group score distributions in each cognitive domain. Methods: Retrospective neuropsychological data for 26 patients with severe chronic schizophrenia and 34 patients with frontotemporal dementia (behavioural variant) was collated. Neuropsychological measures were categorised into 16 cognitive domains. Raw scores were converted into standardised z -scores for each measure, which were then averaged across measures within each domain. In addition to difference analysis, equivalence testing was utilised, whereby overlap percentages were computed to reflect the amount of score distribution overlap in each domain between groups. Results: A statistically significant difference was observed only in the executive function sub-domain of Switching. Small-to-moderate and moderate effect sizes were noted in four other domains. Equivalence testing showed more than 85% of overlap in score distribution in most domains. Conclusions: Our findings suggest that some patients with severe chronic schizophrenia have cognitive deficits similar in degree and pattern to patients with frontotemporal dementia. The few differences observed between both groups of patients are important for differential diagnostic purposes. One limitation is the retrospective nature of the study. Suggestions for future research include longitudinal follow-up studies of these two patient populations and studies of aspects beyond neurocognition. An implication of our findings is that the 'dementia of schizophrenia' concept may be applicable to patients with severe chronic schizophrenia.